Hidden Effect of Baby Massage on Hyperbilirubinemia - Agustina, Ayuda Nia; Khairunissa, Cantika Gadis (Media Keperawatan Indonesia, 2023)
Hyperbilirubinemia can occur when the level of bilirubin in the blood is more than 5 mg/dL, clinically characterized by the presence of jaundice with physiological and non-physiological causes. The main treatment for cases of hyperbilirubinemia today is phototherapy. However, in recent years there have been alternative interventions carried out, one of which is baby massage. The purpose of this paper is to analyze the effect of giving massage on the bilirubin levels of infants who have hyperbilirubinemia based on empirical studies of the last 10 years. The writing design uses a literature review with inclusion criteria according to the PICOS format. Methods to find sources or articles through the Pubmed, Proquest, Scient Direct, and Google Scholar databases (2016-2021) published in English and Indonesian. The keywords used are related to hyperbilirubinemia and baby massage. Based on the 10 articles reviewed, it was found that baby massage was given 1 to 3 times a day with a duration of 15-20 minutes in every session. Evaluation of bilirubin levels can use serum bilirubin levels or transcutaneous bilirubin levels, besides that giving massage also increases the frequency of defecation which plays a role in removing bilirubin from the baby's body. Baby massage is expected to prevent and treat standardized hyperbilirubinemia so that it can become uniform and as an alternative intervention in reducing bilirubin levels in infants